County-level source-sink balance and carbon allocation of regional peak emissions: Model construction and application - Bianshiyu Tao; Fengping Wu; Jigan Wang; Mingming Zhu; Jie Zhang; Zhencheng Xing (Ecological Indicators)
A fair and precise carbon allocation mechanism is crucial for enabling sub-regions to reduce emissions responsibly and equitably, thereby supporting regional carbon peaking targets. This study integrates both cumulative carbon sources and sinks to analyze the spatial and temporal dynamics of carbon balance, project regional carbon peaking pathways, and develop a county-level carbon allocation model based on the ’equal cumulative per capita net emissions’ principle. An empirical analysis is conducted for Jiangsu Province, one of China’s most developed and carbon-intensive regions. The findings reveal that Jiangsu’s carbon emissions far exceed its carbon sink capacity, resulting in a pronounced carbon imbalance, especially in South Jiangsu counties/districts, such as Jiangning, Changshu, Kunshan, Zhangjiagang, and Jiangyin. Projections indicate that Jiangsu’s total CO2 emissions will peak at 847.6 million tons by 2030, with county-level carbon quotas ranging from –3.4 Mt in Taicang to 30.1 Mt in Shuyang. This variation underscores the necessity of implementing carbon allocation at the county level. The proposed allocation strategy considers both historical cumulative emissions and ecological sinks, ensuring equitable development by safeguarding the rights of less developed regions while protecting the interests of counties/districts with valuable ecosystems, such as Sheyang, Sihong, and Dafeng. These insights offer valuable guidance for policymakers in designing equitable carbon allocation strategies and integrate them with carbon trading markets to achieve cost-effective emissions reduction and support regional carbon peaking goals.